2011
DOI: 10.1097/ta.0b013e31820784ff
|View full text |Cite
|
Sign up to set email alerts
|

Survival of a Patient With Trauma-Induced Mucormycosis Using an Aggressive Surgical and Medical Approach

Abstract: Mucormycosis should be considered in trauma patients with persistent signs of infection after lavage and antibiotics, especially when necrosis or atypical wound presentations are noted. Approaches such as ours using aggressive surgical management and intensive antifungal administration should be instituted once the diagnosis is suspected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 13 publications
0
15
0
Order By: Relevance
“…We found seventeen cases of isolated hepatic mucormycosis in the literature [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27], of which the majority had hematologic malignancy with associated neutropenia and/or cytotoxic chemotherapy. We identified only four cases of isolated hepatic mucormycosis in solid organ transplant recipients, of whom three had liver transplants and one had a kidney transplant ( Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…We found seventeen cases of isolated hepatic mucormycosis in the literature [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27], of which the majority had hematologic malignancy with associated neutropenia and/or cytotoxic chemotherapy. We identified only four cases of isolated hepatic mucormycosis in solid organ transplant recipients, of whom three had liver transplants and one had a kidney transplant ( Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…This is a disease condition without many therapeutic options due to the severity of disease. The standard treatment recommended in rhinocerebral mucormycosis is amphotericin B with debridement, but the combined treatment of amphotericin B plus either an echinocandin or an azole with debridement was shown to improve survival in three cases [10,11]. Drugs that have an FDA approved indication for mucormycosis are amphotericin B with its lipid derivatives, and isavuconazonium sulfate, the pro-drug of isavuconazole, which was not available until 2015 (a year after this patient's death).…”
Section: Discussionmentioning
confidence: 99%
“…There are 2 cases of successful treatment shown in Table 1. [9,10] A study of the 2 cases suggested that in operating on such a special infectious disease, complete elimination of the necrotic tissue and sufficient drainage should be the purpose of the operation. In addition, it may be helpful for the patient.…”
Section: Discussionmentioning
confidence: 99%
“…One patient underwent multiple debridement and drainage, and the other had a splenectomy, subtotal colectomy, terminal ileum resection, and multiple intraperitoneal irrigations. [9,10] The systemic antifungi therapy in both of these patients included amp B, micafungin, and posaconazole. The basic drug regimen is amp B, combined with micafungin, as soon as possible after the diagnosis.…”
Section: Discussionmentioning
confidence: 99%